Immune Checkpoint Inhibitors in Cancer Therapy: Clinical Landscape, Resistance Mechanisms, and Therapeutic Innovations - Qiongyu Zhang; Zhi Qin; Caijuan Guo (MedComm – Oncology, 2026)
ABSTRACT Immune checkpoint inhibitors (ICIs) have revolutionized the treatment of solid tumors, yet only a limited subset of patients achieves durable disease control. While China has emerged as a major contributor to global ICI development, a comprehensive synthesis of recent trial data and resistance mechanisms is urgently needed to guide clinical practice. This review examines the evolving landscape of ICI‐based combination therapies, including regimens that combine ICI with chemotherapy, targeted therapy, antibody–drug conjugates, antiangiogenic agents, and radiotherapy, which have expanded first‐line treatment options across multiple solid tumors and, in selected settings, have improved disease control or survival beyond historical monotherapy benchmarks. An in‐depth analysis of the molecular mechanisms underlying primary and acquired resistance to ICIs is then provided, drawing on recent advances in multiomics. Building on this framework, emerging, mechanism‐matched strategies designed to overcome specific resistance nodes are critically evaluated. Finally, the promise of integrating spatial transcriptomics and artificial intelligence to help shift ICI therapy from empirical combination toward mechanism‐guided precision immuno‐oncology is discussed. By bridging the gap between clinical evidence and molecular insights, this review offers a perspective that may help accelerate the rational design of next‐generation ICI‐based strategies and improve patient outcomes.